Le son peut-il être spectaculaire ? L’exemple de l’art sonore - Céline Eloy (CeROArt : Conservation, Exposition, Restauration d'Objets d'Art)
The spectacular is undeniably related to the visual approach of the exhibitions. The sound art, as immaterial art, is by its nature set against this obviousness. Is it therefore on as free from spectacular ? The analysis of the sound works allows to consider differently the meaning of the word.